Method for testing weather resistance of PVC composite board

By implementing outdoor natural weather resistance test and limit test on PVC composite board, the problem of inaccurate test results in the existing technology is solved, and a comprehensive and reliable evaluation of the weather resistance performance of PVC composite board is achieved, and product quality and use are improved. life.

CN119438051APending Publication Date: 2025-02-14DIANJIN NEW MATERIAL RES INST (XIAMEN) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411314166.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The prior art applies the testing methods for artificial boards to PVC boards, resulting in inaccurate test results and cannot fully reflect the true weather resistance performance of PVC boards.

Method used

A PVC composite board weather resistance testing method is provided, including outdoor natural weather resistance testing and extreme testing. Outdoor natural weather resistance tests include natural light aging test, water absorption performance test and mechanical performance test, and extreme tests include yellowing resistance test, artificial accelerated aging test, water absorption performance test and mechanical performance test.

Benefits of technology

By combining outdoor weather resistance testing under natural conditions and extreme testing under laboratory conditions, the performance changes of PVC composite panels under different environmental factors are comprehensively examined to ensure the reliability of test results and improve product quality and service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119438051A_ABST
    Figure CN119438051A_ABST
Patent Text Reader

Abstract

The invention discloses a method for testing weather resistance of a PVC (polyvinyl chloride) composite board, which comprises the following steps: outdoor natural weather resistance test: carrying out natural light aging test, water absorption performance test and mechanical property test on the PVC composite board; whether the PVC composite board is qualified or not is judged according to the color difference value of the natural illumination aging test, the water absorption thickness swelling rate of the water absorption performance test, the static bending intensity of the mechanical performance test and the change rate of the elastic modulus; and limit testing: carrying out yellowing resistance testing, artificial accelerated aging testing, water absorption performance testing and mechanical property testing on the PVC composite board, and judging whether the PVC composite board is qualified or not according to the chromatic aberration value of the colorimetric reference value of the yellowing resistance testing, the water absorption rate of the water absorption performance testing and the change rate of the static bending intensity and the elastic modulus of the mechanical property testing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of plate testing, and in particular to a method for testing the weather resistance of a PVC composite plate. Background Art

[0002] At present, weather resistance test methods are widely used in the quality assessment of various boards, especially for products that are exposed to outdoor environments for a long time. These test methods are mainly designed based on the basic characteristics of artificial boards. However, due to the significant differences between PVC boards and artificial boards in terms of material composition, structural characteristics and their response to environmental factors, directly applying the test methods for artificial boards to PVC boards may result in inaccurate results and fail to fully reflect the true weather resistance performance of PVC boards. Therefore, it is particularly necessary to develop a weather resistance test method specifically for PVC composite boards. Summary of the invention

[0003] Therefore, it is necessary to provide a method for testing the weather resistance of PVC composite boards to solve the problem that the existing technology of applying the testing method for artificial boards to PVC boards may result in inaccurate results.

[0004] To achieve the above object, the present invention provides a method for testing the weather resistance of a PVC composite board, comprising the following steps:

[0005] Outdoor natural weather resistance test: The PVC composite board is subjected to natural light aging test, water absorption test, and mechanical property test. The PVC composite board is judged to be qualified based on the color difference value of the natural light aging test, the water absorption thickness expansion rate of the water absorption test, and the static bending strength and elastic modulus change rate of the mechanical property test;

[0006] Limit test: The PVC composite board is subjected to yellowing resistance test, artificial accelerated aging test, water absorption test, and mechanical property test. The qualification of the PVC composite board is judged based on the color difference value of the colorimetric reference value of the yellowing resistance test, the water absorption rate of the water absorption test, and the static bending strength and elastic modulus change rate of the mechanical property test.

[0007] Furthermore, the natural light aging test comprises the following steps:

[0008] Provide a sample of PVC composite board, divide the sample into two parts, the upper part is covered with opaque cardboard, leave the sample outdoors where sunlight can be obtained for a preset period of time, and measure the color difference between the upper and lower parts of the sample with a colorimeter.

[0009] Furthermore, in the outdoor natural weather resistance test, the water absorption performance test includes the following steps:

[0010] Two groups of PVC composite board samples are provided, one group of which is edge-sealed. The two groups of samples are placed outdoors where rain and snow are available for a preset period of time. The thickness of the samples is tested at intervals, and the water absorption thickness expansion rate is obtained based on the thickness of the samples.

[0011] Furthermore, in the outdoor natural weather resistance test, the steps of judging whether the PVC composite board is qualified according to the water absorption thickness expansion rate of the water absorption performance test are:

[0012] If the water absorption thickness expansion rate is less than or equal to 0.1%, it means that the stability of the sample is excellent and qualified;

[0013] If the water absorption thickness expansion rate is greater than 0.1% and less than or equal to 1%, it means that the stability of the sample is good and qualified;

[0014] If the water absorption thickness expansion rate is greater than 1% and less than or equal to 1.5%, the stability performance of the sample is poor and unqualified.

[0015] Furthermore, the yellowing resistance test comprises the following steps:

[0016] The PVC composite board sample was placed in a UV aging test chamber with the parameters set to 1.1 W / (m 2 nm)@420nm, to obtain the color difference value of the colorimetric reference value.

[0017] Furthermore, the artificial accelerated aging test comprises the following steps:

[0018] Soaking: Place the sample in a constant temperature and humidity chamber, set the temperature to 50±1℃, and the time to 1h;

[0019] First steam treatment: place the sample in a hot and cold cycle box, set the conditions to 60±1℃, 3h, and 90±1% humidity;

[0020] Freezing: Place the sample in a hot and cold cycle box, set the temperature to -10±1℃, and the time to 20h;

[0021] First drying: Place the sample in a drying oven and set the temperature to 80±1℃ for 3h;

[0022] Second steam treatment: place the sample in a hot and cold cycle box, set the conditions to 60±1℃, 3h, and 90% humidity;

[0023] Second drying: Place the sample in a drying oven and set the temperature to 80±1℃ for 18h;

[0024] Repeat the above steps.

[0025] Furthermore, before the artificial accelerated aging test, the limit test further includes the following steps:

[0026] Conduct preliminary tests on the samples;

[0027] Determine whether the deformation degree of the sample exceeds the threshold. If so, reduce the cycle period of the limit test.

[0028] Furthermore, after the artificial accelerated aging test, the following steps are also included:

[0029] Conditioning treatment: set the environment temperature to T = 20 ± 3 ° C, relative humidity RH = 65 ± 1%, and the conditioning time to 48h.

[0030] Furthermore, in the limit test, the steps of judging whether the PVC composite board is qualified according to the water absorption rate of the water absorption performance test are as follows:

[0031] If the water absorption rate is less than or equal to 2% and there is no warping or deformation, it means that the stability of the sample is good and qualified;

[0032] If the water absorption rate is greater than 2% and less than or equal to 5%, and there is slight expansion, warping and deformation at the edge, it means that the sample is in a state of slight water absorption and is qualified;

[0033] If the water absorption rate is greater than 5%, and there are significant warping deformation and thickness expansion phenomena, it means that the stability performance of the sample is poor and unqualified.

[0034] Furthermore, the mechanical properties test comprises the following steps:

[0035] Test its static bending strength and elastic modulus according to the mechanical test requirements of the national standard GB / T 17657-2022, and obtain the rate of change before and after the test;

[0036] If the change rate is less than or equal to 10%, and there is no warping deformation after the test, it means that the stability of the sample is excellent and qualified;

[0037] If the change rate is greater than 10% and less than or equal to 20%, and there is a slight warping deformation at the edge, it means that the stability of the sample is good and qualified;

[0038] If the change rate is greater than 20% and there is significant warping and deformation, it means that the stability of the sample is poor and unqualified.

[0039] The above technical solution has the following beneficial effects:

[0040] The test method combines outdoor weather resistance tests under natural conditions with extreme tests under laboratory conditions to comprehensively examine the performance changes of PVC composite boards under different environmental factors. The test method can effectively avoid the shortcomings of traditional weather resistance test methods when applied to PVC composite boards, ensuring that the test results are more reliable. Through a comprehensive weather resistance evaluation of PVC composite boards, product quality can be improved, service life can be extended, and strong data support can be provided for subsequent product development. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 Flow chart of the weather resistance testing method of the PVC composite board in this embodiment;

[0042] Figure 2 This is a schematic diagram of a natural light aging test of a sample in this embodiment;

[0043] Figure 3 FIG. 4 is a flow chart of the limit test in this embodiment. DETAILED DESCRIPTION

[0044] In order to explain the technical content, structural features, achieved objectives and effects of the technical solution in detail, the following is a detailed description in conjunction with specific embodiments and accompanying drawings.

[0045] See also Figure 1 This embodiment provides a method for testing the weather resistance of a PVC composite board, comprising the following steps:

[0046] Outdoor natural weather resistance test: The PVC composite board is subjected to natural light aging test, water absorption test, and mechanical property test. The PVC composite board is judged to be qualified based on the color difference value of the natural light aging test, the water absorption thickness expansion rate of the water absorption test, and the static bending strength and elastic modulus change rate of the mechanical property test;

[0047] Limit test: The PVC composite board is subjected to yellowing resistance test, artificial accelerated aging test, water absorption test and mechanical property test. The qualification of the PVC composite board is judged based on the color difference value of the colorimetric reference value of the yellowing resistance test, the water absorption rate of the water absorption test, the static bending strength of the mechanical property test and the change rate of the elastic modulus.

[0048] The test method combines outdoor weather resistance tests under natural conditions with extreme tests under laboratory conditions to comprehensively examine the performance changes of PVC composite boards under different environmental factors. The test method can effectively avoid the shortcomings of traditional weather resistance test methods when applied to PVC composite boards, ensuring that the test results are more reliable. Through a comprehensive weather resistance evaluation of PVC composite boards, product quality can be improved, service life can be extended, and strong data support can be provided for subsequent product development.

[0049] The PVC composite board is composed of a PVC board and a facing material, wherein the facing material may include but is not limited to melamine facing paper, real wood veneer, fireproof board facing and other materials that can be evenly attached to the surface of the PVC board. This test method is described using the fireproof board facing as an example.

[0050] Outdoor natural weather resistance test

[0051] In this embodiment, the outdoor natural weather resistance test method places the sample in an outdoor environment to allow the sample to age naturally, which can be used as a reference for the artificial aging test method.

[0052] In this embodiment, the natural light aging test includes the following steps:

[0053] Provide a sample of PVC composite board, divide the sample into two parts, the upper part is covered with opaque cardboard, and place the sample outdoors for a preset period of time where sunlight can be obtained. Use a colorimeter to measure the color difference between the upper and lower parts of the sample. Specifically, a 50mm*100mm sample can be divided into two parts, the upper part is covered with opaque cardboard, and the lower part is not treated. Figure 2 As shown, place it in a location exposed to sunlight, and the total test time is 4200h (175 days). The test method for color difference value refers to the yellowing color fastness performance test in GB / T 17657-2022 "Test methods for physical and chemical properties of wood-based panels and veneer wood-based panels", and the judgment standard is based on the national standard GB / T 250-2008 "Gray sample card for color change assessment in textile color fastness tests". Yellowing resistance ≥ 4 is qualified; < 4 is unqualified.

[0054] In this embodiment, the water absorption performance test includes the following steps:

[0055] Provide two groups of PVC composite board samples, one of which is edge-sealed. Place the two groups of samples outdoors where rain and snow can be obtained for a preset period of time. Detect the thickness and weight of the samples at intervals. Obtain the water absorption rate and water absorption thickness expansion rate based on the thickness and weight of the samples, where the thickness corresponds to the water absorption thickness expansion rate and the weight corresponds to the water absorption rate. Specifically, the 100mm*100mm samples can be divided into two groups, one for edge-sealing (the edge-sealing glue can be PUR glue), and one for no treatment. The number and size of the samples can be preset according to actual test requirements. Place the samples in a place where rain and snow can reach them. The total test time is 4200h (175 days). Take a point in the middle of the sample and measure the thickness once a week. Calculate the water absorption thickness expansion rate by comparing it with the thickness of the edge-sealed sample.

[0056] Since the sample is placed outdoors for a long time, it is more intuitive to observe the thickness growth of the sample. According to the 24h water absorption rate and water absorption thickness expansion rate measured by the national standard GB / T17657-2022, the length (along the grain direction) and width (cross grain direction) can reflect the water absorption performance and deformation size of the material, and then reflect the dimensional stability of the material. The calculation formula is as follows:

[0057] Thickness expansion rate after water absorption:

[0058] Water absorption:

[0059] Where:

[0060] t2——thickness of the specimen after immersion in water, in millimeters (mm);

[0061] t1——thickness of the specimen before immersion in water, in millimeters (mm);

[0062] m2——mass of the specimen after immersion in water, in grams (g);

[0063] M1——The mass of the specimen before immersion in water, in grams (g).

[0064] In this embodiment, the steps (judgment criteria) for judging whether the PVC composite board is qualified according to the water absorption thickness expansion rate of the water absorption performance test are:

[0065] If the water absorption thickness expansion rate is less than or equal to 0.1%, it means that the stability performance of the sample is excellent and qualified; if the water absorption thickness expansion rate is greater than 0.1% and less than or equal to 1%, it means that the stability performance of the sample is good and qualified; if the water absorption thickness expansion rate is greater than 1% and less than or equal to 1.5%, the stability performance of the sample is poor and unqualified.

[0066] In this embodiment, the steps (judgment criteria) for judging whether the PVC composite board is qualified according to the water absorption rate of the water absorption performance test are: if the water absorption rate is less than or equal to 2%, and there is no warping or deformation, it means that the stability of the sample is good and qualified; if the water absorption rate is greater than 2% and less than or equal to 5%, and there is slight expansion and warping deformation at the edge, it means that the sample is in a slight water absorption state and is qualified; if the water absorption rate is greater than 5%, and there is significant warping deformation and thickness expansion, it means that the stability performance of the sample is poor and unqualified.

[0067] In this embodiment, the mechanical properties test of the PVC composite board includes the following steps:

[0068] Because the tests of static bending strength and elastic modulus are both limit destruction, all test samples are randomly and equally distributed before the test, one group is used for the control group test before the test, and one group is used for subsequent tests. The number of samples can be preset according to actual test needs. The sample is placed in an outdoor environment, and the total test time is 4200h (175 days). The sample size is L = (20t + 50) mm, t is the basic thickness of the specimen, and the width is b = 50mm. The static bending strength and elastic modulus are tested with a universal mechanical testing machine, and the change rate before and after the test is calculated.

[0069] The static bending strength can be calculated by the following formula:

[0070]

[0071] The elastic modulus can be calculated using the following formula:

[0072]

[0073] Limit Testing

[0074] In this embodiment, the yellowing resistance test includes the following steps:

[0075] The PVC composite board sample was placed in a UV aging test chamber with the parameters set to 1.1 W / (m 2 ·nm)@420nm, and obtain the color difference value of the colorimetric reference value. Specifically, a 100mm*100mm sample can be placed in a UV aging test chamber, and the parameter is set to 1.1W / (m 2 ·nm)@420nm, the test duration is 168h (7 days), continuous testing, sample colorimetric reference values ​​before and after the test. By conducting accelerated aging tests in a UV aging test chamber, the effect of long-term exposure of materials in the natural environment can be simulated in a relatively short period of time, greatly shortening the test cycle.

[0076] See also Figure 3 In this embodiment, the artificial accelerated aging test includes the following steps:

[0077] Soaking: Place the sample in a constant temperature and humidity chamber, set the temperature to 50±1℃, and the time to 1h;

[0078] First steam treatment: place the sample in a hot and cold cycle box, set the conditions to 60±1℃, 3h, and 90±1% humidity;

[0079] Freezing: Place the sample in a hot and cold cycle box, set the temperature to -10±1℃, and the time to 20h;

[0080] First drying: Place the sample in a drying oven and set the temperature to 80±1℃ for 3h;

[0081] Second steam treatment: place the sample in a hot and cold cycle box, set the conditions to 60±1℃, 3h, and 90% humidity;

[0082] Second drying: Place the sample in a drying oven and set the temperature to 80±1℃ for 18h;

[0083] Repeat the above steps for 6 times, depending on actual needs. If the cycle is interrupted (such as weekends), the test should be checked frequently for delamination or other damage. If there is obvious damage, it should be recorded.

[0084] Immersion treatment can simulate the impact of a humid environment on the material and test the water resistance of the material. Steam treatment can simulate a high temperature and high humidity environment to test the stability and durability of the material under humid conditions. Freezing treatment can simulate a low temperature environment to check the changes in the physical properties of the material under cold conditions. Drying treatment can simulate a high temperature and dry environment to evaluate the physical properties and dimensional stability of the material under dry conditions. Through a series of strict environmental condition changes, the aging process of the material can be accelerated, thereby quickly identifying the durability and reliability of the material in actual use.

[0085] In this embodiment, after the artificial accelerated aging test, the following steps are also included:

[0086] Conditioning treatment: set the environment temperature to T = 20 ± 3 ° C, relative humidity RH = 65 ± 1%, and the conditioning time to 48h.

[0087] Each cycle needs to be carried out continuously, and the quenching and tempering treatment can be carried out after the complete limit test cycle. The working principle of the quenching and tempering treatment is to place the sample in a standard test environment so that the material reaches a stable base state, thereby ensuring that the initial conditions of each test are consistent. The purpose of this is to stabilize the material performance after the cycle test within a test range and avoid experimental errors.

[0088] In this embodiment, before the artificial accelerated aging test, the limit test further includes the following steps:

[0089] Conduct preliminary tests on the samples;

[0090] Determine whether the deformation degree of the sample exceeds the threshold. If so, reduce the cycle period of the limit test.

[0091] Due to the strict test conditions, a preliminary experiment is required before the test to estimate the test cycle that the PVC composite board can withstand. If the board is found to be severely deformed during the test cycle, the test cycle can be appropriately shortened. However, the subsequent test steps remain unchanged to ensure the accuracy and comparability of the test results.

[0092] Preferably, the artificial accelerated aging test is performed before the water absorption test and the mechanical property test, and the yellowing resistance test can be performed in any order.

[0093] In this embodiment, the water absorption performance test of the limit test can refer to the water absorption performance test of the outdoor natural weather resistance test, and the principles of the two are the same. The judging criteria are: if the water absorption rate is less than or equal to 2%, and there is no warping deformation phenomenon, it means that the stability of the sample is good and qualified; if the water absorption rate is greater than 2% and less than or equal to 5%, and there is a slight expansion and warping deformation phenomenon at the edge, it means that the sample is in a slight water absorption state and is qualified; if the water absorption rate is greater than 5%, and there is a significant warping deformation and thickness expansion phenomenon, it means that the stability performance of the sample is poor and unqualified.

[0094] Specifically, the performance of the board can be preliminarily evaluated according to the degree of bending and warping of the specimen after the limit test, and the water absorption performance of the board after aging can be judged by testing the water absorption rate and water absorption thickness expansion rate of the board for 24 hours. The size of the specimen can be 50mm*50mm. After the specimen has undergone the above-mentioned limit test, its water absorption rate and water absorption thickness expansion rate are measured to judge the excellence of its waterproof performance. According to the 24h water absorption rate and water absorption thickness expansion rate measured by the national standard GB / T17657-2022, the two data of length (along the grain direction) and width (cross grain direction) can reflect the water absorption performance and deformation size of the material, and then reflect the dimensional stability of the material. Because the water absorption thickness expansion rate is not required in the national standard test standard for PVC boards, and the results of the experimental test show that the water absorption thickness expansion rate does not change much, only the water absorption rate can be required for this judgment.

[0095] The method of this embodiment was used to test the water absorption of the following five composite boards with different veneers. All five boards used PUR veneers. The change rates of the test samples before and after were as shown in Table 1 below:

[0096] Table 1 - Water absorption test

[0097]

[0098] The stability of the waterproof performance of the PVC composite board can be clearly seen from the embodiments. The change rates of PVC composite board 3 and PVC composite board 5 are ≤2, so it is judged that their stability performance is excellent; the change rates of PVC composite board 1, PVC composite board 2 and PVC composite board 4 are between 2% and 3%, so it is judged that they have slight water absorption.

[0099] In this embodiment, the mechanical properties test of the PVC composite board includes the following steps:

[0100] The specimen was operated according to the process of the limit test. According to the mechanical test size requirements of the national standard GB / T 17657-2022, the specimen size was L = (20t + 50) mm, t was the basic thickness of the specimen, and the width b = 50 mm. The static bending strength and elastic modulus were tested using a universal mechanical testing machine, and the rate of change before and after the limit test was calculated.

[0101] The mechanical property test of the limit test can refer to the mechanical property test of the outdoor natural weather resistance test, and the principles of the two are the same. Judgment criteria: If the change rate is less than or equal to 10%, and there is no warping deformation after the test, it means that the sample has good stability and is qualified; if the change rate is greater than 10% and less than or equal to 20%, there is slight warping deformation at the edge, it means that the sample has good stability and is qualified; if the change rate is greater than 20%, and the plate has significant warping deformation, it means that the sample has poor stability and is unqualified.

[0102] The method of this embodiment was used to test the mechanical properties of the following four PVC composite boards with different veneers. The samples of the four materials before testing were all taken from the same plate and in the same direction. Because the tests of static bending strength and elastic modulus are both limit destructive tests, six samples were randomly selected as control tests before the limit test, and the values ​​after the test were averaged. The change rates of static bending strength and elastic modulus before and after the test samples, the absolute values ​​of the change rates, are shown in Table 2:

[0103] Table 2- Mechanical properties test

[0104]

[0105] The stability of the mechanical properties of the PVC composite board can be clearly seen from the embodiments. The mechanical stability of the PVC composite board 2 is excellent; the mechanical stability of the PVC composite board 1 is relatively good; and the mechanical stability of the PVC composite board 3 and the PVC composite board 4 is poor.

[0106] The present application is a weather resistance test method for PVC composite boards, which uses natural and artificial accelerated weather resistance control tests to judge the stability of the material through the water absorption performance of the board.

[0107] This application has the following beneficial effects:

[0108] This test method is mainly used to evaluate the weather resistance of PVC composite boards and is applicable to the weather resistance test of various PVC composite boards. This method combines artificial and natural weather resistance tests to show the weather resistance of PVC composite boards in a more comprehensive way. Through this test method, the standard parameters of board tests can be set more flexibly, and the stability of composite boards can be evaluated more clearly, making the test method more comprehensive and convenient, and providing a powerful tool for in-depth evaluation of the weather resistance of PVC composite boards.

[0109] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that the process, method, article or terminal device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or terminal device. In the absence of further restrictions, the elements defined by the sentence "include..." or "comprise..." do not exclude the existence of other elements in the process, method, article or terminal device including the elements. In addition, in this article, "greater than", "less than", "exceed" and the like are understood to exclude the number itself; "above", "below", "within" and the like are understood to include the number itself.

[0110] Although the above embodiments have been described, once those skilled in the art know the basic creative concepts, they can make additional changes and modifications to these embodiments. Therefore, the above description is only an embodiment of the present invention and does not limit the patent protection scope of the present invention. Any equivalent structure or equivalent process transformation made by using the contents of the specification and drawings of the present invention, or directly or indirectly used in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for testing the weather resistance of a PVC composite board, characterized in that: The steps include: Outdoor natural weather resistance test: The PVC composite board is subjected to natural light aging test, water absorption test, and mechanical property test. The PVC composite board is judged to be qualified based on the color difference value of the natural light aging test, the water absorption thickness expansion rate of the water absorption test, and the static bending strength and elastic modulus change rate of the mechanical property test; Limit test: The PVC composite board is subjected to yellowing resistance test, artificial accelerated aging test, water absorption test and mechanical property test. The qualification of the PVC composite board is judged based on the color difference value of the colorimetric reference value of the yellowing resistance test, the water absorption rate of the water absorption test, the static bending strength of the mechanical property test and the change rate of the elastic modulus.

2. The testing method according to claim 1, characterized in that: The natural light aging test comprises the following steps: Provide a sample of PVC composite board, divide the sample into two parts, the upper part is covered with opaque cardboard, leave the sample outdoors where sunlight can be obtained for a preset period of time, and measure the color difference between the upper and lower parts of the sample with a colorimeter.

3. The testing method according to claim 1, characterized in that: In the outdoor natural weather resistance test, the water absorption performance test includes the following steps: Two groups of PVC composite board samples are provided, one group of which is edge-sealed. The two groups of samples are placed outdoors where rain and snow are available for a preset period of time. The thickness of the samples is tested at intervals, and the water absorption thickness expansion rate is obtained based on the thickness of the samples.

4. The testing method according to claim 3, characterized in that: In the outdoor natural weather resistance test, the steps of judging whether the PVC composite board is qualified according to the water absorption thickness expansion rate of the water absorption performance test are as follows: If the water absorption thickness expansion rate is less than or equal to 0.1%, it means that the stability of the sample is excellent and qualified; If the water absorption thickness expansion rate is greater than 0.1% and less than or equal to 1%, it means that the stability of the sample is good and qualified; If the water absorption thickness expansion rate is greater than 1% and less than or equal to 1.5%, the stability performance of the sample is poor and unqualified.

5. The testing method according to claim 1, characterized in that: The yellowing resistance test comprises the following steps: The PVC composite board sample was placed in a UV aging test chamber with the parameters set to 1.1 W / (m 2 nm)@420nm, to obtain the color difference value of the colorimetric reference value.

6. The testing method according to claim 1, characterized in that: The artificial accelerated aging test comprises the following steps: Soaking: Place the sample in a constant temperature and humidity chamber, set the temperature to 50±1℃, and the time to 1h; First steam treatment: place the sample in a hot and cold cycle box, set the conditions to 60±1℃, 3h, and 90±1% humidity; Freezing: Place the sample in a hot and cold cycle box, set the temperature to -10±1℃, and the time to 20h; First drying: Place the sample in a drying oven and set the temperature to 80±1℃ for 3h; Second steam treatment: place the sample in a hot and cold cycle box, set the conditions to 60±1℃, 3h, and 90% humidity; Second drying: Place the sample in a drying oven and set the temperature to 80±1℃ for 18h; Repeat the above steps.

7. The testing method according to claim 6, characterized in that: Before the artificial accelerated aging test, the limit test further includes the following steps: Conduct preliminary tests on the samples; Determine whether the deformation degree of the sample exceeds the threshold. If so, reduce the cycle period of the limit test.

8. The testing method according to claim 6 or 7, characterized in that: After the artificial accelerated aging test, the following steps are also included: Conditioning treatment: set the environment temperature to T = 20 ± 3 ° C, relative humidity RH = 65 ± 1%, and the conditioning time to 48h.

9. The testing method according to claim 1, characterized in that: In the limit test, the steps of judging whether the PVC composite board is qualified according to the water absorption rate of the water absorption performance test are as follows: If the water absorption rate is less than or equal to 2% and there is no warping or deformation, it means that the stability of the sample is good and qualified; If the water absorption rate is greater than 2% and less than or equal to 5%, and there is slight expansion, warping and deformation at the edge, it means that the sample is in a state of slight water absorption and is qualified; If the water absorption rate is greater than 5%, and there are significant warping deformation and thickness expansion phenomena, it means that the stability performance of the sample is poor and unqualified.

10. The testing method according to claim 1, characterized in that: The mechanical properties test comprises the following steps: Test its static bending strength and elastic modulus according to the mechanical test requirements of the national standard GB / T 17657-2022, and obtain the rate of change before and after the test; If the change rate is less than or equal to 10%, and there is no warping deformation after the test, it means that the stability of the sample is excellent and qualified; If the change rate is greater than 10% and less than or equal to 20%, and there is a slight warping deformation at the edge, it means that the stability of the sample is good and qualified; If the change rate is greater than 20% and there is significant warping and deformation, it means that the stability of the sample is poor and unqualified.